Quality Assessment of a Single-phase resonant inverter - Z.A. Jaffery; Sunil Kumar Chaudhary (Institute of Advanced Engineering and Science, 2012)
The authors present the design, simulation and analysis of a single phase voltage source inverter using soft switching techniques. The performance of the inverter has been compared in terms of harmonic contents present in output voltage and current. The research works for a PWM inverter along with a LLCC filter has been investigated. This paper also investigated the performance of the same inverter with a feedback controller with a closed loop feedback path to maintain rated output voltage. This work is helpful for the inverter used in application where high quality ac wave is prime requirementDOI: http://dx.doi.org/10.11591/ijpeds.v2i4.277